Effects of L-Carnitine on blood pressure, VO2 max, and endurance in athletes: Systematic Review - Annisa Lazuardi Larasati; Rani Sauriasari; Arry Yanuar (Green Publisher Indonesia, 2024)
When playing sports, athletes are required to always maintain their health to provide maximum results in their performance. Supplements are products intended to complement nutritional needs, maintain, enhance and/or improve health functions and have nutritional value and/or physiological effects. L-Carnitine is a health supplement that is widely consumed by athletes. L-Carnitine has many effects on the body and the main effects are seen on blood pressure and VO2 max. The aim of this review is to look at the effects of L-Carnitine on blood pressure and VO2 max. It was found that L-Carnitine had more effect on a person's diastolic than systolic at doses of more than 2 grams/day. Meanwhile, the effect on VO2 max was seen in long-term use of 2 grams for 24 weeks and found a significant increase in VO2 max (p<0.05). L-Carnitine does influence blood pressure, VO2 max and is also correlated with endurance, but until now there is still a need for more research to show that the effects produced by L-Carnitine are significant both on blood pressure and VO2 max in athletes.